PETROGENESIS OF GRANIT AND VALUATION OF QUARTZ VEIN FOR PHOTOVOLTAIC ELEMENT AT GRANITOID COMPLEX TANJUNG KUMBANG FORMATION, PASAMAN, WEST SUMATERA. - Imam Agadinata W., M.
Electricity in today's era is one of the basic needs in everyday life. The source of electrical energy is currently still dominated by coal. This energy source has a relatively high potential for environmental pollution and cannot be renewed. Indonesia is rich in renewable energy with a potential of more than 400,000 Mega Watts (MW), 50% of which or around 200,000 MW is solar energy potential. Meanwhile, the utilization of solar energy itself is currently only around 150 MW or 0.08% of its potential. The high cost of making solar power plants is influenced by the availability of raw materials, namely quartz. Quartz in solar cells plays a role in absorbing the spectrum from sunlight. To support the solar cell industry in order to reduce manufacturing costs so that the use of solar cells will be more affordable, quartz studies are needed in veins, one of which is the potential for quartz in veins and granite in the granitoid complex, Tanjung Kumbang, Pasaman West Sumatra. The mineral characteristics of quartz in the research area based on geological mapping data on granite range from 30-40%. The results of the quartz XRD analysis had levels of 23.2% and 28.4%. Based on the results of the XRF analysis, SiO2 levels ranged from 63.13-93.37%. In quartz veins it has levels ranging from 65.41- 99.97%. Quartz in veins has an average of 95.323% in granite having an average content of 77%. Quartz in veins has a content of 18.323% higher than quartz in granite. The volume of quartz in granite was identified at 34,129,385.98 tons and in veins at 1,267,113.40 tons. SiO2 99,81-99,99%, Al2O3 <0,01% Fe2O3 <0,04%%, TiO2 <0,03%, CaO <0,01%, MgO <0,01%, K2O <0,01% dan Na2O <0,01%. Quartz at research location meets quartz criteria for solar cells and can reduce the need for high quality quartz imports. With the potential for high quality quartz in the domestic market, it is expected to reduce the amount of solar cell production costs. The implications of the falling cost of quartz production are expected to reach a wider market of solar cell users.